Psychological Well-Being of Elementary School Teachers: A Systematic Literature Review of Studies From 2024-2025 - Kristiyana, Yosi Imas; Fuad, Nurhattati; Rahmawati, Desi; Kamaludin, Kamaludin (Journal of Educational Sciences, 2026)
Teachers’ psychological well being plays an essential role in supporting effective instruction and fostering positive teacher student relationships in elementary schools. However, increasing administrative workloads, emotional demands, and performance expectations pose serious challenges to teachers’ mental health. This study aims to systematically identify the main determinants of elementary school teachers’ psychological well being, examine intervention strategies discussed in recent literature, and map current research trends. A Systematic Literature Review was conducted in accordance with the PRISMA 2020 guidelines. Articles were collected using Publish or Perish from the Scopus and Crossref databases, limited to peer reviewed journal publications from 2015 to 2024. Following the screening and eligibility process, 40 articles were selected and analyzed using qualitative thematic synthesis and bibliometric mapping with VOSviewer. The findings show that internal factors such as self efficacy, emotion regulation, resilience, and psychological capital are the most consistent predictors of teachers’ psychological well being. External factors including workload, organizational support, school climate, and leadership practices also play a significant role. Overall, teachers’ psychological well being is shaped by the interaction of individual and organizational factors.